APPLICATION OF P3 IN THE KARAWI MA TAHO BOOK IN SHAPING THE CHARACTER OF 2ND GRADE STUDENTS AT SDIT INSAN KAMIL SANTI IN BIMA CITY - Putri Anggriani; Dewi Masitha; Hermansyah Hermansyah (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
The Independent Curriculum is an innovation with the aim of shaping the character of students that reflects Pancasila values in the form of the Pancasila Student Profile. Character formation includes moral values such as honesty, responsibility and a sense of respect, which are crucial aspects of education. The purpose of this study is to analyze the application of P3 through the book Karawi Ma Taho in shaping the character of 2nd grade students at SDIT Insan Kamil Santi, Bima City. This study uses a qualitative method with a case study approach. Data collection techniques were obtained through observation, interviews and documentation. The results of the study show that the Karawi Ma Taho book is effectively used as a behavioral assessment instrument based on P3 values. Student characters such as independence, discipline, religiosity, and mutual cooperation develop significantly. In addition, parental involvement and school culture also strengthened the success of this implementation. This study confirms that the integration of character assessment books in school culture is a careful plan in an effort to instill Pancasila values and the formation of students' character. Overall, the Karawi Ma Taho Book has proven to be an effective medium in fostering students' character holistically.